Implementasi Nilai Tauhid dalam Pembiasaan Ibadah Harian Siswa Madrasah Ibtidaiyah Muhammadiyah Unggulan Kota Gorontalo (Normatif-Teologis) - Pitriyani Mobiliu; Ilyas Daud; Ratni Bt. H. Bahri; Rulyjanto Podungge (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to analyze the application of the value of tawhid in the daily worship practices of students at the Muhammadiyah Unggulan Elementary School in Gorontalo City through a normative theological approach. This study employs a descriptive qualitative method with a field research approach. Data were collected through participant observation and semi-structured interviews with the madrasah principal, Islamic Religious Education teachers, and homeroom teachers involved in the program to foster worship habits. Data analysis was conducted through data reduction, data presentation, and drawing conclusions by combining interpretive-hermeneutic interpretations of the Qur’an and hadith with empirical field data. The research findings indicate that the values of Tawhid are systematically implemented through the Love-Based Curriculum (KBC), which is integrated into various religious activities, such as hadith memorization, review of short surahs from Juz 30, Quranic literacy, Dhuha prayer, congregational Dhuhr and Asr prayers, short religious talks, and Quranic recitation. Although challenges exist, such as limited facilities and low levels of independence among some students, teacher guidance and collaboration with parents serve as key factors supporting the program’s success. Thus, the habit of worship based on a normative-theological approach is effective in strengthening the internalization of the values of Tawhid starting from elementary education.